Side-chain conjugated polymers for use in the active layers of hybrid semiconducting polymer/quantum dot light emitting diodes. Issue 1 (21st October 2015) - Fokina, Ana; Lee, Yeonkyung; Chang, Jun Hyuk; Braun, Lydia; Bae, Wan Ki; Char, Kookheon; Lee, Changhee; Zentel, Rudolf
Abstract : Three monomers, M1–M3, with modified carbazole cores and styrene functionality were polymerized by RAFT. The polymers were then used in the active layers of hybrid polymer/quantum dot light emitting diodes. Abstract : Three monomers, M1–M3, with modified carbazole cores and styrene functionality were prepared for use in the active layers of hybrid polymer/quantum dot light emitting diodes. Utilizing reversible addition fragmentation chain transfer polymerization, side-chain conjugated polymers, P1–P3, with narrow polydispersities and disulfide end groups were obtained. The thermal, optical, and electrochemical properties of the polymers varied depending on the substituents of the carbazole cores. Through the disulfide end groups the polymers were chemically blended with quantum dots to obtain QD/polymer hybrids, which were further used as active layers in light emitting diodes. The fabricated devices retained the superior electroluminescence properties of QDs and showed good device performance with a highest external quantum efficiency of 6.09%. Moreover, a correlation between the HOMO level of the polymer and device performance was identified.